The incidence of malignancies in asbestosis with chrysotile exposure: a large Chinese prospective cohort study - Wang, Jingwei; Huang, Xiaoyun; Ma, Ruimin; Zhang, Qian; Wu, Na; Du, Xuqin; Ye, Qiao (Frontiers in Oncology, 2023)
Background: Asbestos exposure is closely related to the occurrence and development of various malignancies. This prospective cohort study aimed to evaluate the incidence rate and potential risk factors in a cohort of asbestosis patients in China. Methods: The incidence of malignancies was determined in patients who had been exposed to chrysotile asbestos and diagnosed with asbestosis sequentially at Beijing Chaoyang Hospital from 1 January 2007 to 31 December 2019. Cox regression analyses were used to analyze the correlations between clinical variables and asbestosis combined with malignancies. Results: A total of 618 patients with asbestosis were identified, of whom 544 were eligible for analysis. Among which, 89 (16.36%) were diagnosed with various malignancies. The standard incidence rates (SIRs) of patients with asbestosis combined with malignancies were 16.61, 175, 5.23 and 8.77 for lung cancer, mesothelioma, breast cancer, and endometrial carcinoma, respectively. The risks of all malignancies and lung cancer increased with initial exposure before 17 years old, longer asbestos exposure and smoking. Conclusions: The SIRs of patients with asbestosis-related malignancies were significantly increased in lung cancer, mesothelioma, breast cancer, and endometrial carcinoma in a hospital-based Chinese cohort. Smoking and the duration of asbestos exposure increased the risk of lung cancer.